1999
DOI: 10.1073/pnas.96.22.12881
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate infused posttraining into the hippocampus or caudate-putamen differentially strengthens place and response learning

Abstract: A cross-maze task that can be acquired through either place or response learning was used to examine the hypothesis that posttraining neurochemical manipulation of the hippocampus or caudate-putamen can bias an animal toward the use of a specific memory system. Male Long-Evans rats received four trials per day for 7 days, a probe trial on day 8, further training on days 9 -15, and an additional probe trial on day 16. Training occurred in a crossmaze task in which rats started from a consistent start-box (south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
250
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(280 citation statements)
references
References 59 publications
30
250
0
Order By: Relevance
“…D-Serine permitted the disrupted animals to use a proper allocentric strategy, instead of a compensatory idiocentric strategy, and permitted the restructuring of the proper spatial mapping process. Similar facilitation of the allocentric strategy has been described in adult rats receiving local intrahippocampal injection of glutamate (Packard, 1999), showing that increasing glutamatergic activity facilitates spatial mapping abilities of rats.…”
Section: Discussionsupporting
confidence: 71%
“…D-Serine permitted the disrupted animals to use a proper allocentric strategy, instead of a compensatory idiocentric strategy, and permitted the restructuring of the proper spatial mapping process. Similar facilitation of the allocentric strategy has been described in adult rats receiving local intrahippocampal injection of glutamate (Packard, 1999), showing that increasing glutamatergic activity facilitates spatial mapping abilities of rats.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with this hypothesis, post-training intradorsal striatal infusions of glutamate selectively enhance memory in a visibleplatform water maze task in which rats are trained to approach a cued escape platform that is located in a different maze location on each trial (Packard and Teather 1999). Intradorsal striatal injections of glutamate also enhance response learning in a cross-maze task in which a specific body-turn direction is consistently reinforced (Packard 1999).…”
supporting
confidence: 55%
“…The dorsal striatum is hypothesized to be selectively involved in stimulus-response (S-R) learning and memory (for an early proposal involving nonhuman primates, see Mishkin and Petri [1984]), a view supported by findings of task-dependent effects (i.e., double dissociations) following lesion (Packard et al 1989;Packard and McGaugh 1992;Kesner et al 1993;McDonald and White 1993) or post-training drug manipulations of this structure (Packard and White 1991;Packard andTeather 1997, 1999;Packard 1999). It has been suggested that glutamatergic input to the dorsal striatum provides, in part, sensory information underlying the formation of S-R associations (White 1989).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Previous research using a delayed alternation task demonstrated that rats start out typically using a place strategy early in maze training and later switch to a response strategy (Packard, 1999) and this is related to elevated ACh levels in the hippocampus and striatum, respectively (Chang & Gold, 2003b;Pych et al, 2005a;Pych, Chang, ColonRivera, Haag, & Gold, 2005b). The NMTP task is different from spontaneous and delayed alternation in that the to-be-remembered place changes in a random fashion from trial-to-trial.…”
Section: Discussionmentioning
confidence: 98%